2002
DOI: 10.1007/s12031-002-0025-3
|View full text |Cite
|
Sign up to set email alerts
|

AF150(S) and AF267B

Abstract: The M1 muscarinic agonists AF102B (Cevimeline, EVOXACTM: prescribed in USA and Japan for Sjogren's Syndrome), AF150(S) and AF267B--1) are neurotrophic and synergistic with neurotrophins such as nerve growth factor and epidermal growth factor; 2) elevate the non-amyloidogenic amyloid precursor protein (alpha-APPs) in vitro and decrease beta-amyloid (A beta) levels in vitro and in vivo; and 3) inhibit A beta- and oxidative-stress-induced cell death and apoptosis in PC12 cells transfected with the M1 muscarinic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(38 citation statements)
references
References 35 publications
2
35
0
1
Order By: Relevance
“…Furthermore, we investigated the role of other basic residues located in TM2-3L of the ␤ 2 subunit (Arg 269 and Lys 279 ) and found that only the basic residue at position 274 is sensitive to a charge reversal mutation, suggesting that it is uniquely involved in electrostatic interactions important for receptor activation. This study also confirms the importance of TM2-3L of the GABA A -R ␤ 2 subunit in receptor activation, as previously reported for the ␣ 1 , ␣ 2 , ␤ 2 , and ␤ 3 subunits (12,14,18,25). An interesting difference between the ␣ 1 and ␤ 2 subunits was observed here because ␤ 2 (L272A) failed to alter receptor function, whereas the ␣ 1 ortholog (L277A) reduces GABA sensitivity dramatically (EC 50 ϭ 278 M) (26).…”
Section: Characterization Of Mutations In Loops 2 and 7 Of Thesupporting
confidence: 92%
“…Furthermore, we investigated the role of other basic residues located in TM2-3L of the ␤ 2 subunit (Arg 269 and Lys 279 ) and found that only the basic residue at position 274 is sensitive to a charge reversal mutation, suggesting that it is uniquely involved in electrostatic interactions important for receptor activation. This study also confirms the importance of TM2-3L of the GABA A -R ␤ 2 subunit in receptor activation, as previously reported for the ␣ 1 , ␣ 2 , ␤ 2 , and ␤ 3 subunits (12,14,18,25). An interesting difference between the ␣ 1 and ␤ 2 subunits was observed here because ␤ 2 (L272A) failed to alter receptor function, whereas the ␣ 1 ortholog (L277A) reduces GABA sensitivity dramatically (EC 50 ϭ 278 M) (26).…”
Section: Characterization Of Mutations In Loops 2 and 7 Of Thesupporting
confidence: 92%
“…The M1 mAChR agonists xanomeline and AF267B (Fisher et al , 2002;Caccamo et al , 2006) were synthesized in the laboratory of Medicinal Chemistry at the Feinstein Institute for Medical Research by following previously published methodology (Supplementary Figures 1 and 2) and oxalate salt forms of the compounds were used in experiments. Atropine sulfate and atropine methyl nitrate were purchased from Sigma.…”
Section: Methodsmentioning
confidence: 99%
“…M1 receptor agonists (AF102B, AF150(S) and AF267B-1) which increase synaptic ACh levels are related to improved cognition in various animal Alzheimer's disease models (Fisher et al 2002) and antagonists of presynaptic M2 receptors (which decrease ACh) enhance cognitive ability in rodents and non-human primates (Carey et al 2001). CHRM2 has been shown to be involved in long-term potentiation (Calabresi et al 1998), which is thought to be a fundamental mechanism in learning and memory (Silva 2003), and single nucleotide polymorphisms (SNPs) have been associated with visual evoked brain oscillations suggesting at least a role for CHRM2 in higher mental functioning in humans (Jones et al 2006), although reports that CHRM2 polymorphisms are associated with alcoholism and depression (Comings et al 2002;Edenberg and Foroud 2006;Luo et al 2005;Wang et al 2004) suggest a nonspecific phenotype.…”
Section: Introductionmentioning
confidence: 99%